Effective videoconferencing : techniques for better business meetings - Diamond, Lynn (Crisp Pub. Menlo ParkUS, 1996)
Focuses on how to plan and conduct two-way videoconferencing. Shows advantages of videoconferencing and demonstrates how to evaluate costs and savings. Presents step-by-step instruction on preparing the story board; and detailed videoconferencing guidelines. Includes tips for setting up the room; on appearanace and numbers of participants; and on overcoming nervousness. Presents 3 key skills for videoconferencing meetings.